Cigarette smoking is associated with increased diastolic blood pressure among Chinese nonagenarians/centenarians. (June 2014) - Dong-Qing, Zhao; Chang-Quan, Huang; Yan-Ling, Zhang; Bi-Rong, Dong; Qing-Xiu, Liu
Abstract Objective. Cigarette smoking has been confirmed as a factor influencing arterial blood pressure. In the present study, we studied whether cigarette smoking habits were still associated with arterial blood pressure among Chinese nonagenarians/centenarians. Methods. The present study analyzed data from a survey conducted on all residents aged 90 years or more in the DuJiangYan district (in total 2, 311, 709 inhabitants) in 2005. Results. The individuals included in the statistical analysis were 216 men and 445 women. Individuals who were heavy smokers (76.62 ± 13.28 mmHg) had higher diastolic blood pressure, compared with medium and light smokers (72.33 ± 12.98 and 70.28 ± 10.31 mmHg) (F = 3.551, p = 0.030). There was a higher prevalence of diastolic hypertension (21.62% vs 5.75% and 7.14%, χ2 = 6.302, p = 0.043). Furthermore, there was a higher risk for diastolic hypertension in heavy smokers (OR = 3.886, 95% CI 1.241–12.161) (adjusted) compared with medium (OR = 1.475, 95% CI 0.599–3.360) and light smokers (1.00 reference). There was, however, no significant difference in systolic blood pressure or prevalence of systolic hypertension among the different smoking groups. Conclusions. In summary, we found that among Chinese nonagenarians/centenarians, heavy smoking (current or former) could increase diastolic blood pressure and prevalence of diastolic hypertension, but was not associated with changes in systolic blood pressure.